Aramaic Daniel: a textual reconstruction of chapters 1-7 - Suchard, Benjamin (Studia Semitica Neerlandica, 2022)
The first half of the book of Daniel contains world-famous stories like the Writing on the Wall. These stories have mostly been transmitted in Aramaic, not Hebrew, as has the influential apocalypse of Daniel 7. This Aramaic corpus shows clear signs of multiple authorship. Which different textual layers can we tease apart, and what do they tell us about the changing function of the Danielic material during the Second Temple Period? This monograph compares the Masoretic Text of Daniel to ancient manuscripts and translations preserving textual variants. By highlighting tensions in the reconstructed archetype underlying all these texts, it then probes the tales’ prehistory even further, showing how Daniel underwent many transformations to yield the book we know today